Effect of Psychoeducation Group Training Based on Problem-Solving Skills for Women Experiencing Bipolar Spouse Abuse - Seyyedi Nasooh Abad, Maryam (Front Public Health, 2021)
Aim: Wives of patients with bipolar disorder as informal caregivers are at high risk for spouse abuse and need to learn coping strategies such as problem-solving skills to manage problematic situations. The purpose of this study was to assess the effectiveness of the psychoeducation group training based on problem-solving skills for women experiencing bipolar spouse abuse. Methods: A randomized clinical trial design was used for this study. In intervention group, women experiencing bipolar spouse abuse participated in four problem-solving skills training sessions and women in two groups (intervention = 30 and control = 30) completed the Index of Spouse Abuse at baseline and after 2 months. Results: The results indicated that changes in abuse scores (physical, non-physical and total of Index of Spouse Abuse) after the intervention were significantly different among the two groups (p < 0.0001). Although abuse scores decreased in both the intervention and the control groups, but lower abuse scores in the intervention than control group were statistically significant. Conclusion: Our findings support that the problem-solving skills training intervention can help to decrease the women experience of bipolar spouse abuse.